2004
DOI: 10.1111/j.1532-5415.2004.52402.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Physician Orders for Life‐Sustaining Treatment Program in Oregon Nursing Facilities: Beyond Resuscitation Status

Abstract: The POLST program is widely used in Oregon nursing facilities. A majority of individuals with DNR orders requested some other form of life-extending treatment, and advanced age was associated with orders to limit treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 11 publications
4
88
2
5
Order By: Relevance
“…41,42 A national registry could incorporate the state models such as Oregon, that have been successful at making DNR orders accessible to EMS providers. 43,44 This will increase the likelihood that a patient's DNR wishes are respected, even in the setting of out-of-the hospital cardiac arrest. 45 Improving physician knowledge of the DNR process 46 should also reduce the burden on family members who are asked to make these decisions under stress or when they are unsure of their family member's wishes.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 A national registry could incorporate the state models such as Oregon, that have been successful at making DNR orders accessible to EMS providers. 43,44 This will increase the likelihood that a patient's DNR wishes are respected, even in the setting of out-of-the hospital cardiac arrest. 45 Improving physician knowledge of the DNR process 46 should also reduce the burden on family members who are asked to make these decisions under stress or when they are unsure of their family member's wishes.…”
Section: Discussionmentioning
confidence: 99%
“…West Virginia and New York have similar programs under slightly different names, and several more states are developing similar programs. The orders generally address cardiopulmonary resuscitation, hydration, and feeding (36). Hopefully, other interventions such as dialysis would be included by the physician, particularly if ARF could be predicted, such as in patients with pre-existing chronic kidney disease.…”
Section: Preferences Of the Patient Or Proxymentioning
confidence: 99%
“…POLST was found to be an effective tool in studies that examined whether treatments provided at the end of life matched the orders on the form, [3][4][5] though far less research has been done to evaluate whether POLSTorders truly reflect patient wishes; this is an important area where further research would be useful. 6 Additionally, the TRIAD (The Realistic Interpretation of Advance Directives) studies showed misunderstandings among various healthcare workers regarding the interpretation of advance directives and related documents.…”
mentioning
confidence: 99%